Korporacje jako podmiot etyczny a koncepcja degrowth economy - Pogonowska, Barbara (Człowiek i Społeczeństwo, 2018)
Barbara Pogonowska, Korporacje jako podmiot etyczny a koncepcja degrowth economy [Corporates as a ethical units regarding ‘degrowth economy’ concept] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 175–185, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The article attempts to present a selective part of sphere of corporate social responsibility idea and practice’ evaluation. This idea and practice have been compared to some official EU & UN documents and ‘degrowth economy’ concept.